Tensile Behavior of Directed Energy Deposited Bi-Metallic Ti-Ni-Based Alloy at Interfacial Area - Chen, Yitao; Rios, Cesar Ortiz; Liou, Frank (JOM (1989), 2025)
A Ti-Ni-based bi-metallic shape memory alloy was fabricated using directed energy deposition, and the tensile testing behavior at two sections after post-heat treatments were focused. The Ti-rich Ti-Ni-Cu ternary shape memory alloy was first fabricated on a TiNi shape memory alloy with near-equiatomic composition to achieve multi-functional shape memory behaviors using powder-based additive manufacturing. The bi-metallic part then underwent 400°C and 600°C heat treatment at the interfacial area, and the interfacial area was subject to tensile loading and unloading. The digital image correlation technique was applied to extract the tensile stress-strain behavior and map out the local strain evolution of different shape memory alloy sections of the bimetallic structure. Significant differences in the local stress-strain behaviors of martensitic and austenitic TiNi phases were observed and discussed among various heat-treatment effects. The tensile study in this work indicates the strong capability of the directed energy deposition process to develop multi-sectional shape memory alloys with unique combined memory effects, and those unique mechanical behaviors can be clearly recorded and evaluated by digital image correlation.